How emergency nurses cope and motivate themselves to sustain their caring work: An integrative literature review. Issue 7 (29th August 2021) - Rantung, Gilny; Griffiths, Debra; Plummer, Virginia; Moss, Cheryle
Abstract: Aims and objectives: The aim of this integrative review was to assess how emergency nurses cope and motivate themselves to sustain their caring work. Background: The need to enhance sustainability of the workforce creates a demand to consolidate contemporary evidence related to emergency nurses' motivations, how they cope and sustain themselves for caring work. Design and methods: The integrative literature review informed by Whittemore and Knafl involved searching four databases, which yielded 977 published research papers (2008–2021). A total of 33 studies met the inclusion and quality assessment criteria. The PRISMA checklist for review was followed. Results: No studies addressing all three areas (motivations, coping and caring sustainability) together were identified. Integration of evidence from quantitative and qualitative research was achieved in three categories: (1) emergency nurses' motivations to sustain their work, (2) emergency nurses' coping strategies and (3) sustaining care as emergency nurses. Conclusion: To sustain themselves in caring work, emergency nurses need to be intrinsically and extrinsically motivated and know how to cope effectively with stressors and work demands. There is need for research examining the relationships between these aspects of emergency nursing work. Relevance to clinical practice: To ensure the sustainability of emergency nurses' work and careers understanding of the factors that influence and sustain their motivations and coping strategies is important for nurses and their clinical leaders and managers.